Quality education in science programs: challenges and opportunities in teaching chemistry and physics field / Shahida Hanum Kamarullah, Nur Sha’adah Zainuddin and Wan Noni Afida Ab Manan - Kamarullah, Shahida Hanum; Zainuddin, Nur Sha’adah; Ab Manan, Wan Noni Afida (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Science programs at universities are essential for preparing students for careers in business, research, and teaching. Physics and chemistry present certain challenges regarding their experimental nature, mathematical rigor, and abstract concepts. The cornerstone of assisting students in improving their critical thinking and problem-solving abilities is the provision of high-quality education in university science programs, especially in chemistry and physics. This article explores the opportunities and difficulties of teaching these subjects with an emphasis on two aspects: teaching strategies and student engagement. Moreover, assess the strategies to enhance teaching and learning in chemistry and physics, highlighting their potential to overcome common barriers.